Respuesta :

Answer:

x = -4

y = -4

Step-by-step explanation:

Since y = x, we can say:

x = 2x + 4

-x = 4

x = -4

And now we can substitute -4 in for x, in the equation y = x

y = -4

Hope this helps!

Answer:

(-4,-4)

Step-by-step explanation:

set 2x + 4 and x equal to each other since they both equal 'y'

2x+4 = x

subtract 2x from each side to get:

4 = -x

divide by -1 so the variable becomes positive

-4 = x

if x=-4 and y=x then y=-4 also (you can check this by graphing each equation)

ACCESS MORE